2010
DOI: 10.4293/108680810x12924466008448
|View full text |Cite
|
Sign up to set email alerts
|

Single Incision Laparoscopic Pancreas Resection for Pancreatic Metastasis of Renal Cell Carcinoma

Abstract: Results of this study suggest that single incision laparoscopic subtotal pancreatectomy may be safely performed in centers experienced with advanced laparoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
49
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 11 publications
2
49
0
2
Order By: Relevance
“…Ability to perform lymphadenectomy is one advantage in performing a standard resection; at this point, there is insufficient evidence to advocate whether or not a lymphadenectomy is required in this settingall that is certain is that the overwhelming majority of surgeons have favoured "typical" resections up to this point. Meanwhile, surgical technique continues to evolve in new and exciting directions, with reports emerging of single-incision laparoscopic pancreatectomy for RCC metastases [40].…”
Section: Discussionmentioning
confidence: 99%
“…Ability to perform lymphadenectomy is one advantage in performing a standard resection; at this point, there is insufficient evidence to advocate whether or not a lymphadenectomy is required in this settingall that is certain is that the overwhelming majority of surgeons have favoured "typical" resections up to this point. Meanwhile, surgical technique continues to evolve in new and exciting directions, with reports emerging of single-incision laparoscopic pancreatectomy for RCC metastases [40].…”
Section: Discussionmentioning
confidence: 99%
“…in the english literature, to the best of our knowledge, there are only four papers with only five cases of single-port pancreas resection (1,3,7,13) . The main reason is that the majority of systems available for single site laparoscopic surgery need special articulating instruments, use of small laparoscopes with poor triangulation.…”
Section: Discussionmentioning
confidence: 99%
“…First, retraction is significantly limited. To overcome this problem some surgeons use stay sutures with straight needles to improve retraction (1,3,13) . Another issue is the triangulation.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that reduced-port or single-port laparoscopic surgery is frequently performed for standard laparoscopic procedures including appendectomies, cholecystectomies, and colectomies. [5][6][7] Barbaros et al 8 reported the first single-incision laparoscopic DP performed in a 59-year-old female to treat pancreatic metastasis from renal cell carcinoma. Since then, the number of cases treated with laparoscopic single port (LSP) or laparoscopic reduced port (LRP) DP procedures has increased (Fig.…”
mentioning
confidence: 99%